Influence of pH, light, food concentration and temperature in Aedes aegypti Linnaeus (Diptera: Culicidae) larval development - Torres, Pedro Felipe Fróio; Baldinotti, Heloísa da Silva; Costa, Diogo Andrade da; Miranda, Ceres Maciel de; Cardoso, André Franco (EntomoBrasilis, 2022)
Aedes aegypti Linnaeus mosquito is a vector of several viruses that cause diseases of medical and veterinary importance. Dengue, yellow fever, Zika and Chikungunya viruses are more important arboviruses transmit by mosquitoes. A. aegypti life cycle goes through 4 stages of development and the time for development from egg to adult mosquito depends on a series of biotic and abiotic factors such as temperature, food availability and population density, studied in different species of insects. In this work we studied the effects of different food concentrations, temperatures variation, pH gradient and luminosity on the development of A. aegypti larvae. The eggs were collected in the city of Tangará da Serra/MT and larvae in the L1 stage were used for the tests. The results showed that all the factors studied interfered in the larval development. The increase in food concentration and temperature accelerated the development of larvae to pupae. The acidic pH (pH = 4) proved to be unsuitable for the development of larvae (100% lethality), with the ideal pH for the development of larval stages being equal to pH = 6. Although in all light variations (dark, light and photoperiod 10L/ 14D) there was complete development of the larvae, the photoperiod test proved to be more adequate. This study helps to better understand the success, dispersion and adaptation of the A. aegypti mosquito in different regions under different environmental conditions.